Variabel-variabel yang Memengaruhi Status Jam Kerja Lansia di Provinsi Gorontalo Tahun 2020 - Denita Dwi Andiany; Suryanto Aloysius (Politeknik Statistika STIS, 2022)
The economic condition of the elderly in Indonesia is still quite worrying, forcing the elderly to keep working. Especially in Gorontalo Province, there are still many elderly people who work an excessive number of working hours (>40 hours a week). The high working hours cannot be ignored because it can endanger the health of the elderly. Therefore, a research analysis was conducted on the variables thought to have an effect on the working hours of the elderly. The data source used is the March 2020 Susenas Kor micro data. Descriptive and inferential analysis with binary logistic regression was used to achieve the objectives of this study. The results showed that the tendency of older workers to work excessively was found in elderly men, including the young elderly group (60-69 years), married status, household size of more than 7 household members, did not have pension insurance, and the work status is working with the help of permanent workers/paid workers.